2020
DOI: 10.3138/cjpe.69535
|View full text |Cite
|
Sign up to set email alerts
|

Toward Learning from Change Pathways: Reviewing Theory of Change and Its Discontents

Abstract: The concept of Theory of Change (ToC) is well established in the evaluation literature, underpinning substantial research and practice efforts. However, its ability to facilitate learning has been increasingly critiqued. The objective of this paper is to identify, characterize, and evaluate concerns over the use of ToCs based on a review of relevant studies. Seven concerns are found: distinguishing ToCs from other evaluation approaches, conceptual vagueness, under-developed ToCs, contributing theoretical knowl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…The identification of assumptions underlying the change processes was not found to be particularly difficult, as typically reported in ToC case studies ( 34 ); however, one participant emphasized some assumptions were large and require dedicated interventions to address them. A big assumption, for example, is that SafePORK can contribute to the development of food safety certification.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The identification of assumptions underlying the change processes was not found to be particularly difficult, as typically reported in ToC case studies ( 34 ); however, one participant emphasized some assumptions were large and require dedicated interventions to address them. A big assumption, for example, is that SafePORK can contribute to the development of food safety certification.…”
Section: Discussionmentioning
confidence: 90%
“…Combining ToC and OM can address some criticisms associated with each approach. For example, ToCs can sometimes be seen as vague, generic, and simplistic ( 34 ). This case study demonstrated that developing progress markers for certain outcome pathways can provide further detail into outcome indicators that are typically missing in ToCs.…”
Section: Discussionmentioning
confidence: 99%
“…The criteria for the theory-of-change analysis involved well-defined and measured results following a logical sequence within a plausible timeframe [35][36][37][38][39]. The Environmental Education Program was administrated within the plausible timeframe of the academic year 2021/2022, where pre-tests and post-tests using the survey were conducted.…”
Section: Methodsmentioning
confidence: 99%
“…From the review of existing literature, the framework for environmental education programs, which lead to improved environmentally friendly behavior in undergraduates, needs to be further developed. This research attempts to construct a theory of change [7,[35][36][37][38][39] involving in the improvement of undergraduates' environmental awareness, attitudes, norms and efficacy, as well as an increase in environmentally friendly behavior as the ultimate environmental outcome, in order for stakeholders to learn from experience and continue to challenge existing assumptions; the following hypotheses are proposed: Hypothesis 1 (H1): The Tzu Chi University Environmental Education Program's lessons involving environmental and sustainability topics will significantly improve the environmental awareness and attitudes of undergraduates from the Experimental Group.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation